ANALISIS PERJANJIAN KERJA WAKTU TERTENTU PADA CV. BINTANG PRATAMA WIDYA TEKNIK BERDASARKAN UNDANG – UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI PUTUSAN PENGADILAN NEGERI BANDUNG NOMOR 88/PDT.SUS-PHI/2020/PN BANDUNG) - Chevita Natalie Vania; Amad Sudiro (Jurnal Hukum Adigama, 2020)
CV. Bintang Pratama Widya Teknik hired 4 workers or laborers with Fixed Term of Labor Contract verbal agreement (without written agreement). These 4 workers have worked for 5 to 9 years and eventually got fired. When they were working there, they got a lower salary than the minimum wage of the city domicile. Also they didn't get BPJS for health and employment. The workers also got fired without following the Labor's Law. According to Labor's Law number 13 of 2003, agreement of employment must be made in writing and the period of the agreement is just 2 years with an additional 1 year for seasonal job. These 4 workers filed a lawsuit to the State Court Bandung and according to Labor's Law number 13 of 2003, the court has decided that CV. Bintang Pratama Widya Teknik has to rehire those workers in a written agreement for an uncertain time. The dismissal was also canceled because it didn't in accordance with the law. The company has to pay those workers in accordance with their rights during their dismissal period.